Carbon sequestration potential of Eucalyptus plantations in the central agroclimatic zone of Telangana state - Ravula, Rohith; Milkuri, Chiranjeeva Reddy; Mhaiskar , Priya Rajendra; Bodiga, Sreedhar; Sihag, Kapil; Mallavajjhala, Ram Charan Sharma (Indian Journal of Agroforestry, 2023)
Productivity and economic analysis of Eucalyptus plantations were conducted in two land use patterns in the Central Telangana Zone, namely TSFDC plantations and farmland raised plantations, in seven- and four-years age gradations, respectively, and economics were computed. Total biomass (AGB+BGB), carbon stocks (tree carbon + SOC) and carbon sequestration potential were analysed. For examining the economic feasibility of plantations, economic methodologies such as benefit-cost ratio (BCR), internal rate of return (IRR), net present value (NPV), and net returns were used. The volume of TSFDC managed Eucalyptus plantations ranged from 6.97-118.54 m3 ha-1 and 10.03-93.94 m3 ha-1 in farmland Eucalyptus plantations. Total biomass of TSFDC Eucalyptus plantations from 7.26 t ha-1 - 123.47 t ha-1 and 10.45 t ha-1 - 97.85 t ha-1 in farmland Eucalyptus plantations. The tree carbon stocks of TSFDC Eucalyptus plantations ranged from 3.42 t ha-1 - 58.03 t ha-1 and 4.91 t ha-1 - 45.99 t ha-1 in farmland Eucalyptus plantations. The soil organic carbon of TSFDC Eucalyptus plantations ranged between 24.29-36.29 t ha-1 and 17.50 - 35.70 t ha-1 in farmland Eucalyptus plantations. The carbon sequestration potential of TSFDC Eucalyptus plantations had the potential of sequestrating 115.69 – 580.79 t ha-1 whereas the farmland Eucalyptus plantations had the potential of sequestrating 22.41 – 81.69 t ha-1. TSFDC Eucalyptus plantations had significantly greater net returns (Rs.2,61,564.70 ha-1) than farmland Eucalyptus plantings (Rs.1,16,282.70 ha-1), with B:C ratios of 2.70 and 2.54 and IRR of 27% and 34%, respectively.